The hypoxic microenvironment of Candida albicans biofilms shapes neutrophil responses - Juszczak, Magdalena; Brankiewicz, Aleksandra; Zawrotniak, Marcin; Rapala-Kozik, Maria (Frontiers in Immunology, 2025)
IntroductionThe microenvironment of Candida albicans biofilms create a hypoxic microenvironment, which exerts a profound influence on host immune responses during infection. Neutrophils are key defenders against C. albicans; however, the impact of biofilm-induced hypoxia on neutrophil function remains unclear.MethodsWe co-cultured human neutrophils in vitro with C. albicans biofilms at various stages of maturation, using both wild-type strains and extracellular matrix (ECM)-deficient mutants. Intracellular hypoxia was assessed using a fluorescent oxygen-sensitive probe. Neutrophil effector functions were evaluated by measuring caspase-3/7 activity, stabilization of hypoxia-inducible factor 1-alpha (HIF-1α), and accumulation of the anti-apoptotic Mcl-1 protein. Analyses included also quantification of reactive oxygen species (ROS) production, neutrophil extracellular trap (NET) formation, chemokine secretion (IL-8 and MIP-1β), and neutrophil elastase release. To assess the role of hypoxia signaling in neutrophil responses, cells were treated with the selective HIF-1α inhibitors LW6 and PX478.ResultsNeutrophils infiltrating C. albicans wild-type biofilms experience progressive hypoxia, which intensifies with biofilm maturation. This hypoxia results from high fungal metabolic activity and extracellular matrix (ECM) production. Within the biofilm microenvironment, neutrophils exhibit increased stabilization of HIF-1α and Mcl-1, elevated secretion of MIP-1β, IL-8, and reduced caspase 3/7 activity, collectively suggesting a biofilm-induced pro-survival phenotype. Simultaneously, mature biofilms markedly suppress NET formation and ROS production while enhancing degranulation. Comparative analyses using mannan-deficient C. albicans mutants highlight the critical role of ECM composition in modulating hypoxia-driven immune responses. Pharmacological inhibition of HIF-1α with LW6 and PX478 partially restores NETosis and ROS production, underscoring the pivotal role of this protein in regulation of neutrophil function.DiscussionThese findings provide novel insights into the impact of biofilm-induced hypoxia on neutrophil responses, identifying HIF-1α as a key regulator of immune adaptation in fungal biofilms. Targeting hypoxia pathways may offer new therapeutic strategies to modulate neutrophil responses and enhance host defenses against fungal infections.